Environnements et habitats magdaléniens dans le centre du Bassin parisien - Taborin, Yvette (Documents d'archéologie française, 1994)
The application of different analytical methods (sedimentology, malacology, palynology, anthracology. micromorphology, archaeozoology, radiocarbon and thermoluminescence dating) to a research programme has brought together informations concerning the way Magdalenian groups were implanted and organised in the centre of the Paris basin. In this synthesis, the interaction of all these results are coordinated, which enables the reader to discover and appreciate the multiplicity of contacts established between the prehistoric communities observed and their environment on one hand, and between prehistorians and their subject on the other.